Pengaruh Kompetensi Sumber Daya Manusia, Pemanfaatan Teknologi Informasi dan Fungsi Badan Pengawas terhadap Kualitas Laporan Keuangan - I Putu Adi Mahendra; Sang Ayu Putu Arie Indraswarawati; I Wayan Budi Satriya (UNHI Press, 2023)
The progress of LPD depends on the quality of the financial statements generated. Financial statements are said to be qualified if they meet four characteristics, namely relevant, reliable, comparable, and understandable. The purpose of this research is to find out the effect of human resource competencies, the use of information technology and the function of supervisory bodies on the quality of financial statements (empirical studies on the LPD in Buleleng subdistrict). The population in this study is all employees and supervisory bodies which amounted to 198 people with 63 people selected as research samples. Sample capture uses a non probability sampling method with purposive sampling techniques. Data analysis techniques include validity tests, reliability tests, descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, F tests, R2 tests, and t tests. Based on the results of the analysis shows that the competence of human resources does not have a significant effect on the quality of financial statements. While the use of information technology and the function of supervisory bodies has a positive and significant effect on the quality of financial statements.